Produksi dan keuntungan usaha ternak puyuh sebagai pendapatan alternatif - Poli, Z; Elly, F H; Husain, J (ZOOTEC, 2021)
PRODUCTION AND PROFIT OF QUAIL FARMING AS AN ALTERNATIVE INCOME. The demand for livestock products every year had increased, so it needs to be balanced with its availability. Local poultry including quail can be developed to support self-sufficiency in providing food sources of animal protein. Quail had the prospect of being developed considering the city of Manado as a foreign tourist destination and its population tends to increase. Youth of Ulil Albab Mosque as a group that had introduced the quail farming business. The problem was the extent to which the success of the quail livestock business introduced by the Youth Group of Ulil Albab Mosque. This study was conducted with the aim of knowing the production and profitÂ of quail farming as source of alternative income. The research method was survey method, the sample was determined purposively. The data collected were primary and secondary data. Respondents were youth group of the Ulil Albab Mosque on the Unsrat Campus determined by purposive sampling of 4 people. The data analysis was descriptive. The success of quail business depends on the characteristics of the group members. The business was developed as many as 200 heads with egg production increasing every day. Egg marketing was through online. Quail egg consumers were housewives. Purchases of eggs were made for consumption by family members. In conclusion, egg production of quail business of the Ulil Albab Mosque Youth group increased and the profits obtained were positive with R/C value of 1.38 Suggestion, it is necessary to expand the business so that the maximum consumption of quail eggs can be increased.